(untitled) (Geologica Macedonica, 2020)
This paper deals with preparation of Geographic Information Systems (GIS) landslide inventory for the Polog region. A number of activities were undertaken for this purpose, such as: analysis of own data on landslides, visits of the sites noted in the surveys filled by municipalities, digitizing of landslides from old geological maps in scale 1:25000, analysis and digitizing of landslides from the archive of the Geological Survey of Macedonia, interviews with employees and retired colleagues from geotechnical companies, analysis of landslides along the channels of the “Mavrovo” system, visit to the National University in Tetovo and joint site visit, and visits to several geotechnical companies in Macedonia. Since this is the first attempt to create a regional landslide inventory in N. Macedonia, the adopted structure of the inventory is presented in the paper. Moreover, to see what benefits can be gained from the availability of such inventory some of the most important findings regarding the landslides are presented further. Currently the inventory consists of 136 occurrences, and in time it should be appropriately updated. The main findings related to the distribution and characteristics of the landslides show that future analyses should include preparation of landslide susceptibility/hazard models both for shallow and deep landslides, as well as for flow-like type of slides. In the following stages of investigation, it is planned to analyze a LIDAR (LIght Detection and Ranging) survey that is being prepared for the region and incorporate more landslides in the inventory. Also, findings of the InSAR (Interferometric Synthetic Aperture Radar) analysis will be combined with the inventory, which will lead to conclusions on the movement rates of detected sites. The latter two approaches will be presented in future papers.